Sustainable Cities: A Proposed Environmental Integrity Index (EII) for Decision Making - Shathy, Shagufta T.; Reza, Mohammad I. H. (Frontiers in Environmental Science, 2016)
Urban population has been increasing at an unprecedented rate accommodating more than half of the world population in cities. Massive human intervention in the tropical region contributes to loss of environmental integrity amplifying challenges like air pollution, deforestation, water scarcity, local extinction and destruction of natural landscapes. To shape the international community’s attitude towards economic, social and environmental development regarding environmental integrity different methods- Reducing Emissions from Deforestation and Forest Degradation (REDD+), Clean Development Mechanism (CMD) - are introduced. However, these methods have some limitations along with opportunities. This paper reviewed and analyzed existing methods in order to promote environmental integrity in the rapidly growing urban settings. Based on the drawbacks of current methods a new Environmental Integrity Index (EII) is proposed where indicators are selected while considering social, economic and environmental aspects. The index aims to combine data from field surveys, GIS and remote sensing, and economic and social analysis. We anticipate that this proposed index can support planning for sustainable cities by promoting environmental integrity and balancing biological and ecological components in a highly intricate urban system.